Citogenética como ferramenta no estudo da biodiversidade de lambaris (Characiformes: Characidae) coletados à jusante do Rio Iguaçu, Parque Nacional do Iguaçu, Brasil - Paiz, Leonardo Marcel (2013)
Fish represent the largest group and occupy a more basal position in the phylogeny of vertebrates, contain large morphological variety and are present in different habitats, making it an interesting model for the study of genetic variability and evolution. Among these, for species popularly known as minnows, growing numbers of systematic and phylogenetic studies are presented, primarily due to the discovery of synonyms and description of new species. In the present study we analyzed cytogenetically seven species of minnows (abramis A., A. asuncionensis, A. correntinus, Astyanax sp., M. dichroura, R. and T. descalvadensis argenteus) collected downstream of the Iguazu Falls (Lower Basin Paraná River), and this stretch corresponding to the area of environmental preservation of the Iguassu National Park. It is species-specific markers, such as karyotypic macrostructure, pattern of heterochromatin distribution and localization of 5S rDNA genes and 18S rDNA. The results help to distinguish between A. abramis and A. asuncionensis, the first cytogenetic data of A. correntinus suggested correlation with group A. schubarti due to the high similarity of karyotypes. The analysis astyanax sp. confirmed case of a species not yet described taxonomically. The analyzes Moenkhausia, Roeboides Tetragonopterus and showed the first molecular cytogenetic data, revealing variability in the number and location of sites of 5S rDNA and 18S rDNA, confirming the diversity of these genes among different genera of Characidae, and allowing the use of these markers in comparative analyzes with congeneric species